Modeling functional relationships between morphogenetically active radiation and photosynthetic photon flux density in mango tree crown - Carrié, Emma; Grechi, Isabelle; Boudon, Frédéric; Frak, Elzbieta; Combes, Didier; Normand, Frédéric (Frontiers in Ecology and Evolution, 2023)
Light is a key factor in plant ecophysiological modeling because of its crucial effects on plant growth and development. However, solar light quantity and quality change with environmental factors such as sky condition and solar elevation. When passing through a tree crown, light is modified by its interaction with the phytoelements, leaves and axes. This leads to a variability of light quantity and quality within the crown, with consequences on light-related processes such as photosynthesis and photomorphogenesis. We evaluated the effects of positional (depth within the crown) and environmental (sky condition, solar elevation) factors on light quantity and quality within the crown of the tropical evergreen mango tree. Functional relationships were modeled between morphogenetically active radiation variables that describe light quality (narrowband red (Rn), narrowband far-red (FRn), the ratio ζ=Rn:FRn, and UVA-blue (UVA-BL)) and light quantity (photosynthetic photon flux density (PPFD) and relative transmitted PPFD (TrPPFD)). Light quantity and quality varied within the mango tree crown in a wide range similar to that of a forest. This variability was structured by the depth within the crown as well as by sky condition and solar elevation. Linear relationships linked Rn, FRn and UVA-BL to PPFD, and non-linear relationships linked ζ to TrPPFD. These relationships were strong, accurate and unbiased. They were affected by positional and environmental factors. The results suggested that these relationships were shaped by the characteristics of incident solar light and/or by the interactions between light and phytoelements. Two consequences of interest emerged from this research: i) the modeled relationships allow to infer light quality, that is difficult and time-consuming to simulate, from light quantity modeling within a tree crown, and ii) sky condition and solar elevation should be considered to improve light modeling within a tree crown.